Biocompatible choline iodide catalysts for green living radical polymerization of functional polymers - Wang, Chen-Gang (2019)
Herein, nontoxic and metabolizable choline iodide analogues, including choline iodide, acetylcholine iodide, and butyrylcholine iodide, were successfully utilized as novel catalysts for “green” living radical polymerization (LRP). Through the combination of several green solvents (ethyl lactate, ethanol, and water), this green LRP process yielded low-polydispersity hydrophobic, hydrophilic, zwitterionic, and water-soluble biocompatible polymethacrylates and polyacrylates with high monomer conversions. Well-defined hydrophobic–hydrophilic and hydrophilic–hydrophilic block copolymers were also synthesized. The accessibility to a range of polymer designs is an attractive feature of this polymerization. The use of nontoxic choline iodide catalysts as well as green polymerization conditions can contribute to sustainable polymer chemistry.